The determinants of sukuk issuance: evidence from top sukuk issuing countries / Mohamad Nizam Jaafar ...[et al.] - Jaafar, Mohamad Nizam; Muhamat, Amirul Afif; Abdul Karim, Norzita; Basri, Mohd Faizal; Hasmadi, Amer Alir (Accounting Research Institute (ARI), 2021)
Macroeconomic variables may influence the issuance of Sukuk. The purpose of this study was to determine the relationship between macroeconomic variables namely Gross Domestic Product (GDP) per capita, inflation, rules of law, corruption of control and political stability. This study used a panel data study consisting of 11 countries that were mostly involved in the issuance of Sukuk. The countries are Bahrain, Brunei Darussalam, Indonesia, Kuwait, Malaysia, Pakistan, Qatar, Saudi Arabia, Singapore, Turkey and United Arab Emirates. The data was generated from 2006 until 2015 and collected from the authorized sources such as the Islamic Finance Information Services (IFIS), World Development Indicator and World Economic Outlook. This research employed several statistical methods like descriptive statistics, unit root test, and correlation analysis. In order to meet the objective of this research, an econometrics estimation of Pool Ordinary least square model, Fixed Effect Model and Random Effect Model were tested. The output from the Fixed Effect Model indicates that only GDP and control of corruption have a significant relationship to Sukuk issuance. It can be concluded that when the GDP increases, the number of Sukuk issued will increase accordingly. This is also applicable to corruption where better control of corruption will lead to an increase in Sukuk issuance. Therefore, good policies should in place to ensure a conducive economic environment that will encourage participation in the Sukuk market.